Case report: A case of complete resolution of obstructive and central sleep apnea with Cheyne Stokes breathing in a patient with heart failure 60 days post-left ventricular assist device implantation - Mashaqi, Saif; William, Michael; Quan, Stuart F.; Combs, Daniel; Estep, Lauren; Patel, Salma I.; Sahni, Jyotsna; Parthasarathy, Sairam (Frontiers in Sleep, 2023)
Sleep-disordered breathing (obstructive and central sleep apnea) are common in patients with heart failure with reduced ejection fraction. Herein, we report a 69-year-old patient with a history of severe heart failure and refractory ventricular arrhythmia who was diagnosed with a moderate degree of obstructive and central sleep apnea with Cheyne Stokes breathing. He underwent a successful implantation of left ventricular assist device. Our patient had a complete resolution of both obstructive and central sleep apnea 60 days post-LVAD implantation as confirmed by home sleep apnea test.